Ensino policial militar - Luiz, Ronilson de Souza (2008)
The present thesis investigates in which way the professional qualification of the São Paulo State policemen can contribute for improvement in redering the service of public security. The core of the thesis borns in the necessity of abandoning, in what it will be necessary, the military paradigm and implanting a new paradigm on the basis of the following principles: formation and continued professional qualification, interdisciplinary, integration, comprehensive and capillarity, beyond the basic permanent modernization. In this direction, it was prioritized the attempt of to understand the lack of investment in the professional qualification. One inquered to analyze the relation between the visible practice of police and the process of teaching to be a policeman. The thesis was constructed in teh basis of the questioning of the professional qualification, analyzing the way as the policemen are formed. Over all from 1988, with the changes operated in the social and political plan, the contest is challenged for the society, which is to elaborate politics of public security and crime control that do not compromise the advances conquered after the redemocratização of the country. In the search of the construction of a security and citizening policy, it wascarried out interviews with three retired colonels who had directed police academies. The inquiry also was carried out on the basis of a document of the Ministry of Justice, called of National Curriculum Source, of 2004,. As theoretical subsidy, it was supported in researchers who express their envolvement with the proposal of a humanise formation, especially Paulo Freire and of Luiz Eduardo Soares. The institucional and bibliographical analysis, beyond the state of the art on policy, had corroborated for the confirmation the devaluation of the academic formation for the exercise of the police activity. While process, proposals for a professional formation continued are presented, and they are considered a prerequisite in the search of excellency in the redering the service of public security. We believe that all policeman naturally can exceed positively its paper, also acting as educator, in with refers to prevention. The work finishes disclosing a urgent necessity of if stimulating, investing and to value the professional qualification, searching less endogenous and humanize formation